- two *x*(x - five)/(x^ two - twenty-five)^ two + one /(x^ two - twenty-five) = zero
minus 2 multiply by x multiply by (x minus 5) divide by (x squared minus 25) squared plus 1 divide by (x squared minus 25) equally 0
minus two multiply by x multiply by (x minus five) divide by (x to the power of two minus twenty minus five) to the power of two plus one divide by (x to the power of two minus twenty minus five) equally zero
-2*x*(x - 5)/(x2 - 25)2 + 1/(x2 - 25) = 0
-2*x*x - 5/x2 - 252 + 1/x2 - 25 = 0
-2*x*(x - 5)/(x² - 25)² + 1/(x² - 25) = 0
-2*x*(x - 5)/(x to the power of 2 - 25) to the power of 2 + 1/(x to the power of 2 - 25) = 0
-2x(x - 5)/(x^2 - 25)^2 + 1/(x^2 - 25) = 0
-2x(x - 5)/(x2 - 25)2 + 1/(x2 - 25) = 0
-2xx - 5/x2 - 252 + 1/x2 - 25 = 0
-2xx - 5/x^2 - 25^2 + 1/x^2 - 25 = 0
-2*x*(x - 5) divide by (x^2 - 25)^2 + 1 divide by (x^2 - 25) = 0